(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Irritable Bowel Syndrome (IBS) is a functional gastrointestinal disorder characterized by varying bowel habits and recurrent abdominal pain. An observational study conducted on 25 patients of IBS who attended the Kayachikitsa O.P.D, V.P.S.V Ayurveda college, Kottakkal noticed Muhurbadha muhurdrava varchas (Increased frequency of loose stools after meals)- 88%, Saruja malapravrithi (abdominal pain during defaecation)- 60%, Daha (burning sensation)- 60% and Sleshmasamsrishta mala (mucus in stools)- 52% as the common presentations. On assessing the symptoms, Grahani dushti, Agnimandya, Arsas and Tridosha involvement can be found predominating in the pathophysiology. Kaidaryadi kashayam is a well known traditional decoction formulation from the text Chikitsa manjari- Mahodara chikitsa. This yoga having Tridoshahara, Kleda soshana, Pachana deepana, Vatanulomana and Grahani balya property is found to be effective in reducing the symptoms of IBS, when administered along with suitable formulations. Kaidaryadi kashayam contain 4 drugs i.e., Zingiber officinale, Murraya koeinigii, Terminalia chebula and Tricosanthes dioica. The action of Kaidaryadi kashayam is evaluated for its action on IBS based on available clinical and research data here in this paper. The ingredients inhibits proton pump, thereby reducing the gastric secretion, helps in the protection of gastric mucosa, reduces the acidity of gastric juice and acts as a strong cytoprotective. So based on the available data we can say Kaidaryadi kashayam is an effective formulation in the management of Lower GIT pathology of IBS.